Perancangan Dan Implementasi Sistem Keamanan Jaringan Menggunakan Alienvault Pada SMK N 4 Kota Bengkulu - Gita Dahlia Lestari; Juju Jumadi; Ahmad Asyhari (UNIVED Press, 2026)
This study aims to design and implement a network security system using AlienVault OSSIM at SMK N 4 Kota Bengkulu. The method used in this research is the Network Development Life Cycle (NDLC), which consists of analysis, design, simulation, implementation, monitoring, and management stages. AlienVault is implemented as a standalone operating system running on a virtual machine using VMware and is utilized to perform centralized network monitoring, threat detection, and security management. System testing is conducted using the black box method by simulating attacks such as port scanning and ping flooding. The test results show that AlienVault is capable of detecting network activities, identifying connected devices, and providing alerts for suspicious activities. With the implementation of this system, network security at SMK N 4 Kota Bengkulu becomes more controlled, secure, and supportive of teaching and learning activities.